Problematika Pengakuan Hukum Adat dan Kepastian Hukum dalam Surat Pernyataan Waris di Bawah Tangan Berbasis Konsep Purusa - I Ketut Abdi Jayantara; Dewa Ayu Putri Sukadana; I Nyoman Budiana; Agung Ayu Intan Puspadewi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the legal uncertainty surrounding privately executed Statements of Inheritance (Surat Pernyataan Waris/SPW) in Indonesia, particularly when such documents are grounded in the purusa concept of Balinese customary law. While previous studies have discussed either evidentiary law or customary inheritance separately, limited attention has been given to their intersection within the framework of legal pluralism. This research aims to examine the legal validity of SPW under Indonesian positive law and to assess its evidentiary strength when influenced by the purusa principle. The study employs a normative legal method using statutory and conceptual approaches, focusing on provisions of the Indonesian Civil Code and constitutional recognition of customary law. The findings indicate that an SPW, as a private deed, has limited probative value and cannot serve as conclusive evidence without acknowledgment or supporting proof. Although the purusa concept provides strong sociocultural legitimacy in determining heirs, its application does not automatically fulfill formal legal requirements. Consequently, an SPW based on purusa must be aligned with the national legal system to ensure legal certainty and enforceability in inheritance disputes.